2005
DOI: 10.3748/wjg.v11.i10.1521
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of interferon-alpha in combination with chemoradiation on human pancreatic adenocarcinoma

Abstract: AIM:To determine whether IFN- is the agent that turns a slightly effective treatment (radiochemotherapy) into a potent therapy, we tested IFN- for its synergistic properties. METHODS:Eight pancreatic carcinoma cell lines were treated with the single agents and combinations of these. The role of IFN- regarding a) direct inhibitory effects; b) radio and chemosensitizing effects; c) anti-angiogenic properties and d) enhancement of immunogenicity was investigated. RESULTS:Our results show that IFN- has direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…All cell lines tested secreted high amounts of IL-6, TGF-␤ , VEGF and IL-8. The levels were much higher than those observed for example in pancreatic carcinoma [26], breast carcinoma [27] or in various hematological malignancies which might be of major importance. IL-6 has been described as an intracrine growth factor for renal carcinoma cell lines [28] .…”
Section: Discussionmentioning
confidence: 61%
“…All cell lines tested secreted high amounts of IL-6, TGF-␤ , VEGF and IL-8. The levels were much higher than those observed for example in pancreatic carcinoma [26], breast carcinoma [27] or in various hematological malignancies which might be of major importance. IL-6 has been described as an intracrine growth factor for renal carcinoma cell lines [28] .…”
Section: Discussionmentioning
confidence: 61%
“…Most of the toxicities are thought to be related to cisplatin. Furthermore, in vivo data indicate that the combination of 5-FU and INF-α2b is responsible for the anti-tumour effect [ 12 , 13 , 16 , 17 ]. Moreover, there are data supporting the idea that radiotherapy is of low effectiveness [ 2 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include: 1) the radio-sensitization effects of INF-α2b and 5-FU [ 9 , 10 ]; 2) enhanced 5-FU based bio-availability; 3) a synergistic inhibition of pyrimidine metabolism with 5-FU and 4) an independent immunomodulatory effect of INF-α2b [ 11 ]. Furthermore, our own data derived from the translational program accompanying the CapRI trial showed especially immunomodulatory and anti-angiogeneic effects of INF-α2b [ 12 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the best studied agents is interferon alpha (IFN-α), which is a pleiotropic cytokine with multiple functions including enhancing antiviral and antitumoral responses. IFN-α has been shown to enhance the differentiation and function of DCs and macrophages, promotes CD8 + memory responses, and also enhances the activity of natural killer (NK) cells [30][31][32][33]. Additionally, IFN-α modulates the activity of the proteosome to produce more immunogenic antigens and simultaneously upregulates MHC class I expression, resulting in an increased immunogenic antigen expression on the cell surface [34].…”
Section: Interferon Alphamentioning
confidence: 99%